Comparisons of GEM-Based Neutron Detectors with 10B/natB-coated Cathode and Ar/CO2 (He/CO2) Gas Flow - Kiadtisak Saenboonruang (Science Faculty of Chiang Mai University, 2019)
Since its invention in 1997, the Gas Electron Multiplier (GEM) detector has been utilized in various applications including high-precision tracking devices in nuclear and particle physics researches. Typically, the standard GEM detector is suitable for ionizing particle detection, however, by introducing neutron converters to GEM, it could also be used as a neutron detector. This article reports properties of the GEM-based neutron detector using different thicknesses and types of boron (10B and natB) coated on the GEM cathode with either Ar/CO2 (70:30) or 4He/CO2 (80:20) gas flow. Two main properties: relative efficiencies and gains, are carefully investigated. Results show that the modified GEM detector is able to detect both thermal and fast neutrons with different characteristics depending on thicknesses and types of boron, types of gas flow, and voltages supplied to the GEM detector. Introduction to GEM detectors, materials used, testing procedures, and results are discussed in this article.